KERUKUNAN UMAT BERAGAMA (Studi Analisis Tentang Non Muslim, Ahlul Kitab & Pluralisme) - Muhamad Arif Mustofa (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2015)
Inter-religious harmony (Analysis study of non muslim, ahlul kitab & pluralism). Weought to live in harmony in this life. As a human being none of us don’t want to live in peace andharmony. But the extrimism of human faith causing them to be egoistic and assumming that theirreligion is the only truth. Allah has mentioned in the qur’an a human created in multi-ethnics, culturesand races. Indonesia consist of multi-ethnics, multi-faiths and religions. This study will discuss aboutnon-muslim, ahlul kitab, and pluralism, and how we live together in harmony? As Human being weought to live together inspite of religious deferences. To live together in harmony is a sunnatullah (thelaw of God). And it mentioned in qur’an several times, which contains the pluralism value, andhermenetic analysis, among them are mentioned in surah Al-Hujaraat Verse 13.